PRAGMATICS. SPEECH ACT THEORY. DISCOURSE ANALYSIS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of three interconnected fields in linguistic study: Pragmatics, Speech Act Theory, and Discourse Analysis. Each of these disciplines goes beyond examining language as a system of rules and instead focuses on how language functions in real-world contexts. Pragmatics explores how context affects meaning, emphasizing the importance of factors like implicature, deixis, and politeness. Speech Act Theory, developed by philosophers J.L. Austin and John Searle, investigates how language is used to perform actions, such as making promises, giving commands, or expressing emotions. Discourse Analysis examines larger units of communication—both spoken and written—to understand how people construct meaning, manage conversational structure, and reflect social power dynamics. Together, these fields provide a comprehensive approach to understanding language as a social tool, highlighting the nuanced ways in which communication shapes and reflects human interaction.